Vaccination in post-tuberculosis lung disease management: A review of the evidence - Nasiri, M.J.; Silva, D.R.; Rommasi, F.; Zahmatkesh, M.M.; Tajabadi, Z.; Khelghati, F.; Sarmastzadeh, T.; Centis, R.; D'Ambrosio, L.; Bombarda, S.; Dalcolmo, M.P.; Galvão, T.; et al. (Pulmonology, 2025)
Post-tuberculosis lung disease (PTLD), as other chronic respiratory disorders, may have infectious complications; some of them can be prevented with vaccinations. So far, no document has discussed the potential role of vaccination in PTLD. Therefore, the objective of this review was to describe vaccination recommendations to prevent infections potentially capable of complicating PTLD. A non-systematic review of the literature was conducted. The following keywords were used: tuberculosis, vaccination, vaccines and PTLD. PubMed/MEDLINE and Embase were used as the search engine, focusing on English-language literature only. We identified 9 vaccines potentially useful in PTLD. Influenza, pneumococcal and anti-COVID-19 vaccinations should be recommended. Patients with PTLD can also benefit from vaccination against shingles. Vaccination against pertussis is mainly relevant during childhood. Diphtheria, tetanus and measles vaccination are recommended for general population and should be considered in patients with PTLD not previously vaccinated. Tdap (Tetanus, diphtheria, and pertussis) booster should be repeated in every adult every ten years. Vaccination against BCG retains its importance during early childhood in countries where TB is endemic. Vaccination deserves to be considered among the strategies to prevent and/or mitigate PTLD complications. Further evidence is necessary to better understand which vaccines have the greatest impact and cost-benefit.